1999
DOI: 10.1093/ndt/14.4.887
|View full text |Cite
|
Sign up to set email alerts
|

The DD genotype of the angiotensin-converting enzyme gene occurs in very low frequency in Australian Aboriginals

Abstract: The D allele of the ACE gene has little or no influence on the renal disease of Australian Aboriginals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 2 publications
2
29
0
Order By: Relevance
“…For the distribution of the ACE I/D polymorphism, the D allele frequency of the Koreans in the present study (39.6%) was much lower than that of African Americans (63%) 11 and Caucasians (64%), 39 but was higher than that of Australian Aborigines (12.6%) 40 and Amerindians (26.5%), 41 and similar to those described for Chinese Han (38%) 42 and mainland Japanese populations (40%). 17 Several reports have shown that ACE I/D polymorphism accounts for half of the variance of plasma ACE levels in the RAAS pathway.…”
Section: Discussionsupporting
confidence: 82%
“…For the distribution of the ACE I/D polymorphism, the D allele frequency of the Koreans in the present study (39.6%) was much lower than that of African Americans (63%) 11 and Caucasians (64%), 39 but was higher than that of Australian Aborigines (12.6%) 40 and Amerindians (26.5%), 41 and similar to those described for Chinese Han (38%) 42 and mainland Japanese populations (40%). 17 Several reports have shown that ACE I/D polymorphism accounts for half of the variance of plasma ACE levels in the RAAS pathway.…”
Section: Discussionsupporting
confidence: 82%
“…However, others have failed to replicate these associations (Schena, D'Altri, Cerullo, Manno, & Gesualdo, 2001;Schmidt, Schone, & Ritz, 1995). The DD genotype of the ACE gene occurs infrequently in Indigenous Australians (Lester et al, 1999), in whom no significant influence on renal disease has been demonstrated. A recent study in a remote Indigenous Australian community has, however, found an association between a common polymorphism of the p53 gene and proteinuria (McDonald et al, 2002).…”
Section: Genetic Explanationsmentioning
confidence: 99%
“…Research on 2 different Indigenous Australian populations has indicated that the genetic regulation of both inflammatory pathways and the RAS is dramatically different to that found in Caucasians [24,25] . Recent research investigating SNPs in the RAS has shown that Indigenous Australians have different allele frequencies compared with other populations, and indeed display polymorphisms not seen in other populations [24,26] . In light of this evidence, it is reasonable to suspect that the genetic regulation of RAS and inflammatory activity is different in Indigenous Australians compared with other population groups.…”
Section: Personalised Medicinementioning
confidence: 92%
“…Research in Indigenous people from Western Australia, Central Australia, and the Tiwi Islands has shown that Indigenous Australians are genetically distinct from all other global populations [24,25,31,32] . Therefore, it is expected that if Indigenous people are to enjoy the benefits of pharmacogenomics and personalised medicine, specific genetic research must be undertaken in Indigenous Australian cohorts to identify genetic determinants of disease risk, prognosis, and response to therapy.…”
Section: The Future Of Genetic Research In Indigenous Peoplesmentioning
confidence: 99%